Diagnosis and management chronic anemia in herpes simplex virus (HSV) type 1 infection - Fitria MAILIZA (Dentistry Faculty, 2022)
Herpes Simplex Virus type 1 (HSV-1) is usually the cause of oral infection. This infection oftenprecedes the development of this chronic anemia, and it is reasonable that the blood in circulation through virusinfectedtissue becomes contaminated with virus particles on the red cell surface. These virus-contaminated redblood cells may stimulate the reticuloendothelial system to produce antibodies that destroy the red blood cells andlead to anemia. Describe the clinical manifestations, pathogenesis, laboratory examination, diagnosis, and therapiesfor managing Chronic Anemia in HSV-1 infections. (HSV) Infection 1 causes infections above the waist majority oforal and pharyngeal and can be transmitted through direct contact with infected individuals. Prodromal symptomspreceded HSV-1 infection for 1 or 2 days consisting of fever, headache, malaise, arthralgia, and submandibularlymphadenopathy; subsequently, small blisters appear and quickly rupture, leaving shallow round discrete ulcers atall portions of the mouth. Diagnosis of anemia and HSV type 1 infection requires a complete history, clinicalexamination, and laboratory examinations (anti-HSV 1 IgG and IgM) or HSV isolation. Symptomatic treatment withantipyretics/analgesics, local antiseptics, vitamins, a soft diet, and adequate fluid intake is usually sufficient.Antiviral medication, either systemically or topically, may help if the infection is identified early in the prodromalstage. Conclusion: Chronic Anemia and HSV Type I infection should be diagnosed and managed with completeanamnesis, clinical manifestation, and laboratory examination.KEYWORDS: Infection, HSV-1, Anemia, Diagnosis, Management